Viral-Mediated Microbe Mortality Modulated by Ocean Acidification and Eutrophication: Consequences for the Carbon Fluxes Through the Microbial Food Web - Malits, Andrea; Boras, Julia A.; Balagué, Vanessa; Calvo, Eva; Gasol, Josep M.; Marrasé, Cèlia; Pelejero, Carles; Pinhassi, Jarone; Sala, Maria Montserrat; Vaqué, Dolors (Frontiers in Microbiology, 2021)
Anthropogenic carbon emissions are causing changes in seawater carbonate chemistry including a decline in the pH of the oceans. While its aftermath for calcifying microbes has been widely studied, the effect of ocean acidification (OA) on marine viruses and their microbial hosts is controversial, and even more in combination with another anthropogenic stressor, i.e. human-induced nutrient load. In this study, two mesocosm acidification experiments with Mediterranean waters from different seasons revealed distinct effects of OA on viruses and viral mediated microbe mortality depending on the trophic state and the successional stage of the plankton community. In the winter bloom situation, viral lysis accounted for 20-100 % of the loss of bacterial biomass per day and was reduced under increased pCO2. Moreover, the abundance of putative large viruses infecting picoeukaryotes tended to be lower under acidification while their putative hosts’ abundance was enhanced suggesting a direct and negative effect on viral-host interactions. In the oligotrophic summer situation, viral mediated carbon fluxes were less important but there was a stimulating trend of OA on viruses through the cascading effect of elevated pCO2 on the autotrophic and heterotrophic production. Eutrophication consistently stimulated viral production regardless the season or initial conditions. Since viral activity shifts the food web towards a more regenerative pathway by fueling the dissolved organic carbon (DOC) pool, the effect of OA on viral lysis alters the carbon fluxes in the planktonic food web boosting the biological carbon pump. However, high nutrient load lowered the negative effect of OA on viral lysis suggesting an antagonistic interplay between these two major global ocean stressors in the Anthropocene.